New Promising Routes in Peptic Ulcers: Toll-like Receptors and Semaphorins - Jacob, Teresa V.; Doshi, Gaurav M. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Peptic ulcers (PU) are one of the commonest yet problematic diseases found to be existing in the majority of the population. Today, drugs from a wide range of therapeutic classes are available for the management of the disease. Still, the complications of the condition are difficult to tackle and the side effect profile is quite a concern. The literature indicates that Toll-like receptors (TLRs) and Semaphorins (SEMAs) have been under study for their various pharmacological actions over the past few decades. Both these signalling pathways are found to regulate immunological and inflammatory responses. Moreover, receptors and signalling molecules from the family of TLRs and SEMAs are found to have bacterial recognition and antibacterial properties which are essential in eradicating Helicobacter pylori (H. pylori), one of the major causative agents of PU. Our understanding of SEMAs, a class of proteins involved in cell signalling, is relatively less developed compared to TLRs, another class of proteins involved in the immune response. SEMAs and TLRs play different roles in biological processes, with SEMAs primarily involved in guiding cell migration and axon guidance during development, while TLRs are responsible for recognizing pathogens and initiating an immune response. Here, in this review, we will discuss in detail the signalling cascade of TLRs and SEMAs and thereby understand its association with PU for future therapeutic targeting. The review also aims at providing an overview of the study that has been into exploring the role of these signalling pathways in the management of PU.
Keywords: Helicobacter pylori